2023
DOI: 10.1111/mve.12637
|View full text |Cite
|
Sign up to set email alerts
|

Global population genetic structure and lineage differentiation of the stable fly, Stomoxys calcitrans

Abstract: The bloodsucking fly, Stomoxys calcitrans (Diptera: Muscidae), is a cosmopolitan pest that transmits potential pathogens mechanically. We conduct phylogeographic analyses of S. calcitrans to resolve its global population genetic structure for establishing baseline of molecular studies. Results from mitochondrial gene suggested that the major divergence of S. calcitrans predominantly occurred 0.32–0.47 million years ago (Mya) and the subsequent diversifications took place during 0.13–0.27 Mya. The Ethiopian reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Afrotropical populations seem the source of S. calcitrans dispersion to other regions. Tsai et al (2023) [45] also performed a detailed study of the phylogeography of S. calcitrans, using 13 populations from Taiwan, 10 specimens from Poland, and all available data in GenBank and BOLD. They confirmed that the likely origin of S. calcitrans is in the Afrotropical region.…”
Section: Phylogeography Of Stomoxys Calcitransmentioning
confidence: 99%
“…Afrotropical populations seem the source of S. calcitrans dispersion to other regions. Tsai et al (2023) [45] also performed a detailed study of the phylogeography of S. calcitrans, using 13 populations from Taiwan, 10 specimens from Poland, and all available data in GenBank and BOLD. They confirmed that the likely origin of S. calcitrans is in the Afrotropical region.…”
Section: Phylogeography Of Stomoxys Calcitransmentioning
confidence: 99%